2016
DOI: 10.5483/bmbrep.2016.49.5.023
|View full text |Cite
|
Sign up to set email alerts
|

A novel IL-10-producing innate lymphoid cells (ILC10) in a contact hypersensitivity mouse model

Abstract: The immunoregulatory cytokine Interleukin 10 (IL-10) protein is produced by various cells during the course of inflammatory disorders. Mainly, it downregulates pro-inflammatory cytokines, antigen presentation, and helper T cell activation. In this study, we show that the ratio of IL-10-producing cells was significantly increased in lineage negative (i.e., not T, B, or leukocyte cell lineages) cells than in lineage positive cells in lymphoid and peripheral tissues. We further observed that IL-10-producing innat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Recently, a new ILC subset [regulatory subpopulation (ILC reg ) or ILC10] has been identified in mice. 49,50 Transcriptome analysis revealed that these cells constitute a unique subset of ILC that produces regulatory cytokine, but did not express the transcription factor forkhead box protein 3 (FoxP3). Murine ILC reg contribute to resolving intestinal inflammation by producing IL-10 and transforming growth factor (TGF)-b.…”
Section: Ilc Precursorsmentioning
confidence: 99%
“…Recently, a new ILC subset [regulatory subpopulation (ILC reg ) or ILC10] has been identified in mice. 49,50 Transcriptome analysis revealed that these cells constitute a unique subset of ILC that produces regulatory cytokine, but did not express the transcription factor forkhead box protein 3 (FoxP3). Murine ILC reg contribute to resolving intestinal inflammation by producing IL-10 and transforming growth factor (TGF)-b.…”
Section: Ilc Precursorsmentioning
confidence: 99%
“…Recently, independent studies in mice demonstrated the capability of ILCs to produce IL‐10. Kim et al showed increased numbers of IL‐10‐producing non T‐, B‐, or leukocyte cell lineage in the model of oxazolone‐induced contact hypersensitivity. These IL‐10‐producing CD45 + CD127 + Sca‐1 + cells were elevated in the axillary, inguinal lymph node, and ear tissue.…”
Section: Plasticity Of Ilcsmentioning
confidence: 99%
“…Kim et al. first proved that IL‐10‐producing innate lymphoid cells are present in various physiological settings and could be involved in numerous immune responses as regulatory cells . It was Wang et al.…”
Section: Regulatory Innate Lymphoid Cellsmentioning
confidence: 99%
“…FOXP3 + Tregs play critical roles in maintaining immune tolerance, an analogous FOXP3-expressing ILC subset has not been defined so far. The lack of adequate characterization has raised the question as to whether a regulatory ILC subset exists.Kim et al first proved that IL-10-producing innate lymphoid cells are present in various physiological settings and could be involved in numerous immune responses as regulatory cells 115. It was Wang et alwho finally identified ILCreg as equivalent to conventional Tregs, as shown by the expression of CD45 and CD127 and the production of suppressive IL-10 113.…”
mentioning
confidence: 99%